Foraging tactics in dynamic sea‐ice habitats affect individual state in a long‐ranging seabird. (3rd August 2020) - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P.; Ropert‐Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G.; Zahn, Sandrine; Descamps, Sébastien
Abstract: Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long‐ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica . Firstly, using GPS tracking and state‐switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β‐hydroxybutyrate) or trophic level (δ 15 N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea‐ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea‐ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea‐ice loss. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Sammendrag: Individer innad i populasjoner er i noe grad forskjellige fra hverandre, og kan dermed påvirkes av miljøet på ulike måter. Individuelle forskjeller, for eksempel i beiteadferd, kan på lang sikt påvirke overlevelse og reproduksjon. Derfor er det viktig å forstå i hvor stor grad individer skiller seg fra hverandre. Vi undersøkte sammenhengene mellom individuelle strategier i beiteadferd og den fysiologiske tilstanden til antarktispetrellen, Thalassoica antarctica, en langtflygende sjøfugl som er godt tilpasset sjøisen i Sørishavet. Vi var spesielt interessert i hvordan sjøishabitatet utenfor hekkekolonien i Dronning Maud land påvirker fuglene. Ved bruk av GPS‐sporing og bevegelsesmodellering testet vi for forekomsten av distinkt beiteadferd (strategier) i vår studiepopulasjon. Vi fant stor variasjon i bevegelsesmønstre og beiteadferd, og funnene våre tyder på en gradient av strategier fra beiting i tett sjøis til beiting i åpent hav. Dernest studerte vi om den fysiologiske tilstanden til fuglene ved retur til kolonien var relatert til individenes strategi. Morfometriske data (vekt og størrelse) og fysiologiske målinger av flere plasmametabolitter ga oss et bilde av individenes tilstand. Dette kombinerte vi med sporingsdata (habitatbruk) hos de samme individene. Resultatene våre indikerer at beitestrategier i liten grad påvirker energibalansen, men kan påvirke andre aspekter av antarktispetrellenes tilstand. Beiting i tettere sjøisområder var relatert til lavere vektøkning i ungeperioden. Den store individuelle heterogeniteten i bestander av antarktispetrell kan redusere konsekvensene av miljøendringer, spesielt konsekvensene av forventet reduksjon av sjøis.